Lipid Oxidation Products on Inflammation-Mediated Hypertension and Atherosclerosis: A Mini Review - Leong, Xin-Fang (Frontiers in Nutrition, 2021)
Cardiovascular diseases such as hypertension and atherosclerosis are the common causes of mortality in developed and developing countries. Repeated heating of the dietary oil is a common practice to reduce cost during food preparation. When the cooking oil is heated at high temperatures, production of free radicals augments the oxidative degradation of lipids and depletes the antioxidant content present in the cooking oil. Chronic intake of foods prepared using reheated oil could impair antioxidant capacity, leading to oxidative stress and inflammation. This review aims to summarize the current evidence of lipid oxidation products on hypertension and atherosclerosis via inflammatory pathway. In particular, toxic lipid oxidation products such as malondialdehyde and 4-hydroxy-2-nonenal are taken into account. Understanding the signaling pathways underlying the pathology associated with the lipid oxidation-derived aldehydes may be useful to develop therapeutic strategies for the prevention of inflammatory-related cardiovascular complications.